2D Undulated Metal Hydrogen-Bonded Organic Frameworks with Self-Adaption Interlayered Sites for Highly Efficient C–C Coupling in the Electrocatalytic CO2 Reduction - Lv, Jianning; Li, Wenrui; Li, Shuai; Xu, Shuo; Lv, Zunhang; Zhu, Zhejiaji; Dai, Lu; Wang, Bo; Li, Pengfei (Nano-Micro Letters, 2025)
The hydrogen-bonded organic frameworks (HOFs) as a new type of porous framework materials have been widely studied in various areas. However, the lack of appropriate active sites, low intrinsic conductivity, and poor stability limited their performance in the field of electrocatalysis. Herein, we designed two 2D metal hydrogen-bonded organic frameworks (2D–M–HOF, M = Cu2+ or Ni2+) with coordination compounds based on 2,3,6,7,14,15-hexahydroxyl cyclotricatechylene and transition metal ions (Cu2+ and Ni2+), respectively. The crystal structure of 2D–Cu–HOF is determined by continuous rotation electron diffraction, indicating an undulated 2D hydrogen-bond network with interlayered π-π stacking. The flexible structure of 2D–M–HOF leads to the formation of self-adaption interlayered sites, resulting in superior activity and selectivity in the electrocatalytic conversion of CO2 to C2 products, achieving a total Faradaic efficiency exceeding 80% due to the high-efficiency C–C coupling. The experimental results and density functional calculations verify that the undulated 2D–M–HOF enables the energetically favorable formation of *OCCHO intermediate. This work provides a promising strategy for designing HOF catalysts in electrocatalysis and related processes. Highlights: 1 Highly crystalline 2D metal hydrogen-bonded organic frameworks (2D-M-HOFs) including 2D-Cu-HOF and 2D-Ni-HOF were designed and synthesized. 2 The 2D-M-HOF with flexible ligands leads to the formation of the self-adaption interlayered sites, which facilitate the C–C couple and overcome the limitations of the coadsorption of multiple intermediates in the electrocatalytic CO2 reduction reaction. 3 The undulated 2D-Cu-HOF exhibits outstanding activity and selectivity for electrocatalytic reduction of CO2 to C2 products with a total Faradaic efficiency of 82.1% (48.2% for C2H5OH and 33.9% for C2H4) at −1.2 V vs. RHE.